Second Five Year Plan a Review of Progress Government of Uttar Pradesh - Planning Commission (Planning Commission, 1962)
The Second Five Year Plan covered the period April 1, 1956 to March 31, 1961. Essentially, this period was a continuation of the efforts begun in the First Five Year Plan. In terms of long-term economic development, the decade 1951—61 constitutes one phase. During this phase, the economy of Uttar Pradesh recovered from the after-effects of war and the consequences of partition. the first efforts of planners were directed towards satisfying the basic needs of the people which had been long neglected—reform of land tenures, local self-Government through village panchayats. improvement of communications, provision of educational and health facilities, amelioration of backward classes.
Government of Uttar Pradesh, Planning Department